De sammenviklede reaktioner og deres destitution: Revolution/kontrarevolution - Juhl, Carsten (K&K - Kultur og Klasse, 2018)
The question of the katechon in the revolution constitutes the central preoccupation of this text. There is still inertia or slowness in the development of uprisings, but the katechon is now independent of any expectation of revelation as in the original biblical edition of the notion or in the modern one (Russia October 1917, Germany November 1918). So, today it is even more open for the reactionary momentum than it has ever been before, and the momentum is incarnated by Continental China as the strongest and most aggressive of the totalitarian states. Reaction has always been dangerous, but the Commune of Barcelona 1936-37 had more space for initiatives and was not suffocated immediately as the Commune of Aleppo was in 2012-13. So, this time the revolution has to be really unilateral and autonomous: no collaboration with reformist parties as in Barcelona or with religious institutions as in Aleppo; they are all vehicles of the reaction.